Symposium 4: Spatial theory in networked learning - Edwards, Richard (Proceedings of the International Conference on Networked Learning, 2014)
Over the years, there has been much discussion of the impact of the internet and new forms of data sourcing and communication for education and the ways in which networked learning breaks down the bounded the institution, classroom, and curriculum. While much attention has been given to the changing spaces of education introduced by new technologies, and the use of spatial metaphors in the framing of educational practices, the impact of spatial theory on the discussion of such education is less well developed. Space is left unexamined as simply a different context, container or backcloth for curriculum and pedagogy. This paper draws upon aspects of spatial theory to examine the ways in which the mobilities and openings made possible by the introduction of technologies also entail mooring and boundary marking in order to give the technologies specifically educational purposes. The paper outlines a number of spatial theories, in particular, the contemporary uptake of theories of (im)mobilities. Work on (im)mobilities has developed from the interplay of post-structuralist theory with complexity and actor-network theory. The paper explores its implications for researching networked learning and suggests that rather than consider education as focussed on practices of learning and teaching, we could more fruitfully consider it as spatial orderings or (im)mobile assemblings in the enactments of curriculum and pedagogy.